2007
DOI: 10.1149/1.2409477
|View full text |Cite
|
Sign up to set email alerts
|

An Isothermal Annealing Study of Spontaneous Morphology Change in Electrodeposited Copper Metallization

Abstract: A systematic investigation of the effect of annealing time and temperature on the incubation period for spontaneous morphology change ͑SMC͒ in electrodeposited copper metallization is reported. Based on an additivity principle derived by Mittemeijer for transformations with an Arrhenius-type dependence of kinetics on temperature, it is shown that the remaining incubation time for SMC at room temperature following annealing at a given temperature should be linearly related to the annealing time. By repeatedly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…It can be seen that, in each case, excellent linearity is obtained over the The plots in Fig. 3 are equivalent to Arrhenius plots 20,21 and may be represented by the equation…”
Section: Resultsmentioning
confidence: 87%
“…It can be seen that, in each case, excellent linearity is obtained over the The plots in Fig. 3 are equivalent to Arrhenius plots 20,21 and may be represented by the equation…”
Section: Resultsmentioning
confidence: 87%
“…The value of D depends only on T and T 0 and so Equation 11 represents a principle that we call the proportionality of corresponding times: 83 for given temperatures T and T 0 the corresponding times τ and τ 0 are related by the same proportionality factor D for all choices of (α 1 ,α 2 ). We note that if the average rate of the process during the induction period τ at temperature T is r = δα δt avg,T = α 2 − α 1 τ and r 0 is the value of r at temperature T 0 , then…”
Section: Arrhenius Analysismentioning
confidence: 99%
“…During this event, smaller particles appear on top of the existing smooth rounded features on the surface of the deposit typically after 0.5-2 h of room-temperature aging. [1][2][3][4][5][6][7][8][9] The metallurgical phenomenon characteristic of such an event, occurring after a short period of time at low temperatures, is generally a recovery process, which involves the activity of point defects, primarily vacancies. Thin films often contain a high concentration of excess vacancies 10 and thus the early stages of thin-film relaxation is probably dominated by a recovery process.…”
Section: Introductionmentioning
confidence: 99%
“…A recent in situ atomic force microscope ͑AFM͒ study revealed that, during room-temperature aging, the surface of freshly electrodeposited polycrystalline copper films can undergo a spontaneous morphology change ͑SMC͒. [1][2][3][4][5][6][7][8][9] Typically, this takes place within a period of 30 min to 2 h after the deposition and occurs suddenly in many cases. We investigated why such a sudden morphology change occurs within a short period of time after the deposition and concluded that this particular film behavior appears to be stress-related.…”
mentioning
confidence: 99%